Brief review of the mathematical models for analyzing and forecasting transmission of COVID-19 - Mustafa, Syed Khalid; Ahmad, M. Ayaz; Sotnik, S.; Zeleniy, O.; Lyashenko, V.; Alzahrani, Othman (JCR, 2020)
Coronaviruses are one of the dangerous sources of human infection. To counter such a source, it is important to obtain reliable statistics. It is also necessary to carry out appropriate data analysis, which helps to find solutions to various issues. To do this, use data analysis and forecasting models. Thus, this work is devoted to the review of mathematical models for the analysis and prediction of the distribution of COVID-19. Such a review showed that there are models of different directions. This allows you to make more effective decisions.
Keywords: mathematical models; COVID-19